Design and Implementation of a Microcontroller-Based Water Turbidity Detector Utilizing the Nephelometric Turbidity Unit Method - Ichwana Putra, Dody; Ekariani, Shelvi (AI Society & STMIK Indonesia, 2023)
The objective of this study is to create a water turbidity detection system, aiding customers of a municipal water supply company in preserving the quality of water for everyday use. The aim is to prevent the mingling of stored clean water with turbid water when the tap is turned on. To achieve this, we employ a smartphone as a remote control device, enabling users to monitor the water's condition remotely. The study's findings demonstrate that this system adeptly manages the water separation process based on its condition, allowing manual control via Bluetooth communication within a maximum range of 10 meters. This setup provides two control options: activating and deactivating the water channel through a solenoid valve. Test outcomes indicate the system effectively segregates the water as per its condition and promptly follows user directives.